AR Ariane de Rothschild : II Prémio de Pintura Lisboa MMV = II Painting Prize Lisbon. - Hedley, Gill; Exhibition. AR Ariane de Rothschild : II Prémio Pintura Lisboa = II Painting Prize Lisbon. Lisboa. Galerie Palácio Galveias Lisboa. Banque Privée Edmond de Rothschild Europe Bruxelles. 2005-10-20. 2005-11-27 (Bruxelles : Banque Privée Edmond de Rothschild Europe Bruxelles, 2005)
Caeiro, Manuel ; Sousa Cardoso, Paula ; Cabanas, Carla ; Frutuoso, Ricardo ; Barateiro, Pedro ; Nesbitt, Jorge ; Costa, Cecilia ; Carvalho, Francisca ; Mesquita, Fernando ; Barata, Hugo ; Canoilas, Hugo ; Cabral, Ines ; Lobo, Gonçalo ; Faria, Isabelle ; Jorge, Joana ; Marçal, Joao ; Lourenço, José ; Pires, Marco ; Costa, Marcelo ; Condado, Maria ; Lusitano, Maria ; Moreira, Nuno ; Nunes-Ferreira, Nuno ; De Sousa, Patricia ; Falcão, Pedro ; Nelson Soares, Pedro ; Cortez Pinto, Rita ; Magalhães, Rita ; Chrystie, Vanessa ; Barata, Vasco
HB : groot formaat : zie speciale kast
Engels
Portugees
boek